The first-generation student experience : implications for campus practice, and strategies for improving persistence and success - Davis, Jeff, 1959 June 5- (Stylus, 2010)
Given that first-generation students comprise over 40% of incoming freshmen, increasing their retention and graduation rates can dramatically increase an institution's overall retention and graduation rates. This book provides administrators with a plan of action to create the awareness necessary for meaningful long-term change, sets out a campus acclimation process, and provides guidelines for the necessary support structures. First-person narratives by first-generation students help the reader get to grips with the variety of ethnic and economic categories to which they belong. The book conc.